Unexpected molecular and morphological diversity of hemichordate larvae from the Neotropics. Issue 4 (27th November 2019) - Collin, Rachel; Venera‐Pontón, Dagoberto E.; Driskell, Amy C.; Macdonald, Kenneth S.; Boyle, Michael J.
Abstract: The diversity of tropical marine invertebrates is poorly documented, especially those groups for which collecting adults is difficult. We collected the planktonic tornaria larvae of hemichordates (acorn worms) to assess their hidden diversity in the Neotropics. Larvae were retrieved in plankton tows from waters of the Pacific and Caribbean coasts of Panama, followed by DNA barcoding of mitochondrial cytochrome c oxidase subunit I ( COI ) and 16S ribosomal DNA to estimate their diversity in the region. With moderate sampling efforts, we discovered six operational taxonomic units (OTUs) in the Bay of Panama on the Pacific coast, in contrast to the single species previously recorded for the entire Tropical Eastern Pacific. We found eight OTUs in Bocas del Toro province on the Caribbean coast, compared to seven species documented from adults in the entire Caribbean. All OTUs differed from each other and from named acorn worm sequences in GenBank by >10% pairwise distance in COI and >2% in 16S . Two of our OTUs matched 16S hemichordate sequences in GenBank: one was an unidentified or unnamed Balanoglossus from the Caribbean of Panama, and the other was an unidentified ptychoderid larva from the Bahamas. The species accumulation curves suggest that nearly all the species have been collected and only one more species might still remain undetected in the Pacific. In contrast, the Caribbean species accumulation curve suggests that further sampling could yield more than 10 additional OTUs. Tornaria from the 14 OTUs exhibited typical planktotrophic morphologies, and, in some cases, may be distinguished by differences in pigmentation and by the number of telotrochal ciliary bands, but in general, few diagnostic differences were detected.